The Effect of the Project-Based Learning Model on Enhancing Fourth-Grade Students’ Understanding of Cultural Diversity in Pancasila Education at SD Negeri 2 Sukodono - Elina Ayu Noviawati; Syailin Nichla Choirin Attalina; Hamidaturrohmah (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Project-Based Learning (PjBL) is an instructional model that involves students directly in project activities. Through these projects, students become more active and engaged in the learning process compared to conventional models, ultimately contributing to improved understanding and memory retention. This study aims to analyze the effect of PjBL on fourth-grade students’ understanding of cultural diversity at SD Negeri 2 Sukodono. A quantitative approach with pre-experimental design with a one-group pretest–posttest structure was employed. Data were collected from 42 students using a validated multiple-choice test administered before and after the PjBL intervention. Results revealed a statistically significant improvement in students’ understanding of cultural diversity at SDN 2 Sukodono. The paired-samples t-test produced a significance value of 0.000 (p < 0.05), leading to rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (Hₐ). The class mean score rose substantially from 71.86 (pretest) to 90.62 (posttest). These findings confirm that the Project-Based Learning model is highly effective in enhancing cognitive mastery of cultural diversity content (traditional musical instruments, regional attire, and customary houses) among elementary students, thereby supporting its wider adoption in Pancasila and civic education curricula.